Case Report: Two cases of immune-associated myocarditis caused by tislelizumab - Zhao, Jie; Wan, Jinliang; Wang, Shan; Zhang, Shuyue; Hao, Yanzhang (Frontiers in Oncology, 2025)
The current phase of immune checkpoint inhibitors has improved the clinical outcomes of many cancer therapies; however, these agents may also lead to some high-consequence immune-related adverse events. We report two cases of cancer patients treated with tislelizumab, one with liver metastases after surgery for rectal cancer and one with non-small cell lung cancer. In both cases, elevated cardiac enzyme markers were observed, and one developed fatal myocarditis, while the other was treated with high-dose methylprednisolone steroid therapy and eventually improved. The probability of immune-associated myocarditis has been reported to be only 0.39%, but once myocarditis occurs, the mortality rate is more than 50%, making it a rare but serious side effect. Here, we discuss the antitumor treatment, the mechanism of immune-associated myocarditis induced by tislelizumab, the evaluation of the association, and the treatment after the development of immune-associated myocarditis in two patients, with the aim of improving clinical awareness of tislelizumab-induced immune-associated myocarditis and promoting timely judgment and appropriate therapeutic measures.